2011
DOI: 10.1111/j.1365-2214.2010.01121.x
|View full text |Cite
|
Sign up to set email alerts
|

Domains of importance for parents, medical professionals and youth with cerebral palsy considering treatment outcomes

Abstract: Background-The aim of this study was to assess the domains of importance in therapeutic intervention for cerebral palsy (CP) using categories of the International Classification of Functioning, Disability, and Health -Version for Children & Youth (ICF-CY).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 8 publications
3
61
1
Order By: Relevance
“…23,27 To our knowledge, only 1 study to date applied the International Classification of Functioning categories to assess domains of importance in therapeutic interventions for children with cerebral palsy. 28 The Vargus-Adams study conducted a survey of youths, parents, and medical professionals (n ¼ 75). Out of 322 responses, the most prevalent categories were related to ''mobility'' (45%) and ''movement related functions'' (45%).…”
Section: Profile Of Functioning By Experts' Perspectivementioning
confidence: 99%
“…23,27 To our knowledge, only 1 study to date applied the International Classification of Functioning categories to assess domains of importance in therapeutic interventions for children with cerebral palsy. 28 The Vargus-Adams study conducted a survey of youths, parents, and medical professionals (n ¼ 75). Out of 322 responses, the most prevalent categories were related to ''mobility'' (45%) and ''movement related functions'' (45%).…”
Section: Profile Of Functioning By Experts' Perspectivementioning
confidence: 99%
“…Our results are generally consistence with, but are more specific than, previous research findings. 12,29,30 Certainly, children with CP and their parents are concerned most often with pain, daily function, participation and community life. As well, the social acceptance, emotions, and family functioning are the discerned areas of life which are associated with QOL of children with CP.…”
Section: Practical Interpretations and Implicationsmentioning
confidence: 99%
“…Hence QOL has gained increasing attention as an important health or intervention outcome measure. 11,12 QOL has been defined by the World Health Organization as individuals' perception of their position in life, in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns. 13 While measuring QOL is a vital part of assessing the wellbeing of children with CP, scales that have been used in the past 14,15 have been found to have substantial limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Vargus-Adams and Martin (2011) asked youth with CP, their parents and health professionals, what they found most important to consider when evaluating the effects of an intervention. The findings showed that the participants endorsed items across all domains of the ICF-CY [57].…”
Section: Discussionmentioning
confidence: 93%